2012
DOI: 10.7314/apjcp.2012.13.12.6285
|View full text |Cite
|
Sign up to set email alerts
|

Does the Increasing Trend of Colorectal Cancer Incidence in Jeddah Reflect a Rise in the Kingdom of Saudi Arabia?

Abstract: Background: The aim of this study was to outline the trend in the incidence of colorectal cancer (CRC) in the city of Jeddah, Kingdom of Saudi Arabia (KSA), for comparison with previously published national CRC data. Materials and Methods: A retrospective data analysis was performed on all cases of CRC diagnosed between January 2000 and December 2006 amongst Saudi patients in Jeddah using data retrieved from the Saudi Cancer Registry (SCR). Descriptive analysis was performed and results were compared to nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 11 publications
2
13
0
Order By: Relevance
“…Similar to earlier reports, this study reiterates that a significant proportion of Malays present at younger age compared to the Chinese and Indians (King and Kutty, 1971). A recent study from Jeddah Saudi Arabia reports mean age of 58 for male and 53 for female (Mosli and Al-Ahwal, 2012) and Iran mean age of 57.7 for male and 56.6 for female (Hajmanoochehri et al, 2014). Possible explanations are yet to be unveiled.…”
Section: Discussionsupporting
confidence: 89%
“…Similar to earlier reports, this study reiterates that a significant proportion of Malays present at younger age compared to the Chinese and Indians (King and Kutty, 1971). A recent study from Jeddah Saudi Arabia reports mean age of 58 for male and 53 for female (Mosli and Al-Ahwal, 2012) and Iran mean age of 57.7 for male and 56.6 for female (Hajmanoochehri et al, 2014). Possible explanations are yet to be unveiled.…”
Section: Discussionsupporting
confidence: 89%
“…It should be mentioned that several studies from different parts of Turkey reported different risk rates ranging from 7 to 16 (14,15). In Saudi Arabia, there was a steady mild increase in the risk of CRC (16)(17)(18). As shown in graph No.1, this risk was half of that of Jordan and Arab Palestinians.…”
Section: Discussionmentioning
confidence: 79%
“…An increased trend in the incidence of CRC in Jeddah between 2000 and 2006 mirrors the recent trend in Saudi Arabia, 25% presenting with distant metastasis and adenocarcinomas accounting for 72% of cases (Mosli and Al-Ahwal, 2012). The five-year OS for 1994-2004 was 44.6% for patients with CRC, rates by stage being generally lower than the typically reported survival rates (Al-Ahwal et al, 2013).…”
Section: Colorectal Cancermentioning
confidence: 76%